Systematics of Modern Benthic Foraminiferal Assemblages From the Deltaic Mangrove Ecosystem of Sundarbans (Journal of the Asiatic Society of Bangladesh, Science, 2021)
The contemporary intertidal foraminifera and estuarine environment information were collected from the four sites adjoining the deltaic mangrove environment in the Sundarbans. The marsh zones of the south-western coastal region of Bangladesh were examined for modern benthic foraminifera and to expound on the relationship of the foraminiferal assemblages with the environment. Due to high inaccessibility and remoteness, the taxonomic study of foraminifera and its depositional environment remains largely overlooked in the Sundarbans of Bangladesh. This study includes a detailed survey of depositional environment of these fluvio-deltaic to shallow marine sediments. The seventeen species belonging to fourteen genera representing nine families were recorded from surficial sediment of supratidal, intertidal, and dune environment of Kotka, Jamtala, Kochikhali, and Dimer char area. In the present study, these foraminiferal assemblages are characterized calcareous and agglutinated foraminifera. The Kotka beach is recognized as Nonionina assemblage zone, Jamtala beach designated as Ammonia assemblage zone, Kochikhali as Nonionina assemblage zone and Dimer char as Rosalina-Nonionina-Nonionella assemblage zone. The deposition of foraminifera is restricted to Sundarbans’ low to high marsh zone.J. Asiat. Soc. Bangladesh, Sci. 47(2): 121-136, December 2021